2020
DOI: 10.1002/nbm.4226
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional correlation MRI

Abstract: Multidimensional correlation spectroscopy is emerging as a novel MRI modality that is well suited for microstructure and microdynamic imaging studies, especially of biological specimens. Conventional MRI methods only provide voxel‐averaged and mostly macroscopically averaged information; these methods cannot disentangle intra‐voxel heterogeneity on the basis of both water mobility and local chemical interactions. By correlating multiple MR contrast mechanisms and processing the data in an integrated manner, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 96 publications
0
43
0
Order By: Relevance
“…Visual inspection of the different injury biomarker maps shown in Figs. 4 and S1 revealed that filtering of the data does not result in loss of the spectral information of interest, and furthermore, the filtered images appear qualitatively of higher quality. Importantly, the data reduction in the case of the filtered data did not significantly affect the resulting injury biomarker maps (Fig.…”
Section: Axonal Injury Spectral Signatures Are Preserved After Filteringmentioning
confidence: 95%
“…Visual inspection of the different injury biomarker maps shown in Figs. 4 and S1 revealed that filtering of the data does not result in loss of the spectral information of interest, and furthermore, the filtered images appear qualitatively of higher quality. Importantly, the data reduction in the case of the filtered data did not significantly affect the resulting injury biomarker maps (Fig.…”
Section: Axonal Injury Spectral Signatures Are Preserved After Filteringmentioning
confidence: 95%
“…By combining both contrast encoding mechanisms into the same sequence, a multi-dimensional characterization of the voxel's microstructural compartments can be performed. [17][18][19][20][21][22] These diffusion-relaxometry experiments typically include multiple echo times (TE) and/or repetition times (TR) to vary the T 2 -and T 1 -weighting, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…While such approaches certainly date back to the 1980s, the actual 2D representation of such datasets has benefitted from the developments of related 2D versions of the ILT algorithm [ 21 ]. T 1 -T 2 correlation maps [ 22 , 23 ] have been instrumental in improving the understanding of discrete or distributed components of spin sets in complex systems such as crude oil [ 24 , 25 ] and food materials [ 26 ], or porous media such as rocks [ 22 , 27 ] and cement paste [ 28 , 29 ] and even biological applications [ 30 ]. However, T 1 -T 2 studies of biological matter are scarce, and the authors are aware of only one recent work where cartilage has been investigated as part of a larger study [ 31 ].…”
Section: Introductionmentioning
confidence: 99%